The Relation between Effortful Control and Language Competence—A Small But Mighty Difference between First and Second Language Learners - Keller, Karin; Troesch, Larissa M.; Loher, Sarah; Grob, Alexander (Frontiers in Psychology, 2016)
The present longitudinal study evaluates the effect of Effortful Control (EC) as a core dimension of temperament on early language competence. We assume that first and second language competence is influenced by EC, and that immigrant children with low EC are thus at risk of an unfavorable language development. The sample consisted of n = 351 dual language learners (DLLs) with an immigrant background and n = 78 monolingual children. Language competence was measured with a standardized language test at age 4.9 years and at age 6.3 years. EC was captured with the Child Behavior Questionnaire, completed by teachers. Results of regression analyses revealed a significant effect of EC on second language development. DLLs with lower EC were found to have not only lower language competence at the beginning and the end of kindergarten but also a less favorable language development. Comparisons between the effect of EC on first and second language provide evidence that EC plays a bigger role in subsequent second language competence compared to first language competence. Overall, the results emphasize the small yet significant role of EC in the second language development of DLLs.